Molekul antar Bintang dan Struktur Galaksi - Bambang Hidajat (Journal of Mathematical and Fundamental Sciences, 1975)
Ringkasan. Tulisan ini merupakan tinjauan ulang penemuan molekul di dalam ruang antarbintang, kemungkinan pembentukannya dan kaitannya dengan struktur Galaktika.Abstract. A review on the discovery of interstellar molecules and the theory of the molecule formation in space are given. The relationship between dense dust cloud and the structure of galaxy is briefly outlined.